(untitled) (Canadian Medical Education Journal, 2020)
Entry into postgraduate medical training in Canada is facilitated through a national application and matching system which establishes matches between applicants and training programs based on each party’s stated preferences. Health human resource planning in Canada involves many factors, influences, and decisions. The complexity of the system is due, in part, to the fact that much of the decision making is dispersed among provincial, territorial, regional, and federal jurisdictions, making a collaborative national approach a challenge. The national postgraduate application and matching system is one of the few aspects of the health human resources continuum that is truly pan-Canadian. This article examines the evolution of the application and matching system over the past half century, the values that underpin it, and CaRMS’ role in the process.